The Use of Subtitle in Cartoon Movie Entitled “Frozen 2” as A Media in Improving Students’ Vocabulary Mastery on SMP Purnama 2 Semarang in Academic Year 2023 - Tanzila Alfi Hasanah; Dyah Nugrahani; Ajeng Setyorini (Social Science Academic, 2023)
The research aimed to investigate the effectiveness of using English subtitles from the movie "Frozen 2" to enhance students' vocabulary mastery. The study employed a quantitative approach with a pre-experimental design and focused on ninth-grade students at SMP PURNAMA 2 SEMARANG. The sample consisted of 25 students selected through purposive sampling. Pre-test and post-test scores were collected to analyze the data. The study found that the use of English subtitles in the movie "Frozen 2" had a significant positive impact on students' vocabulary mastery. The results of the pre-test and post-test scores showed a considerable improvement in vocabulary understanding. The mean pre-test score was 55.36, while the mean post-test score increased to 82.52. The research also assessed the N Gain scores to evaluate the effectiveness of using subtitles in the movie. The average N Gain score was calculated to be 62.08%, indicating that the approach was quite effective in enhancing vocabulary mastery among the students. Furthermore, the study addressed some of the challenges faced by students in vocabulary learning, such as boredom, difficulty in pronunciation, and struggling to remember new vocabulary words. The use of engaging media like movies was highlighted as a way to overcome these challenges and improve students' motivation to learn. In conclusion, the research demonstrated that utilizing English subtitles from the movie "Frozen 2" effectively enhanced students' vocabulary mastery. The N Gain scores reflected a significant improvement in vocabulary understanding, and the approach was found to be quite effective in helping students engage with and remember new vocabulary words.